The prestige economy of elite education: a Baudrillardian analysis of an aspirational English school (UCL Press, 2023)
Academic entrepreneurial behaviours are increasingly a research field paralleling processes of capitalist commodification. We mobilise Baudrillard's concepts to probe a school's strategic communication methods symbolising class neoliberalism, which aspirational parents may experience as a desired habitus of 'distinction'. We suggest their knowledge of class and education, once imported into the interpretation of this school's web presence, will coalesce with its simulacra of elite education. Our account encourages comparisons with selective school websites and utilises the qualitative data on the public site of this school, a methodological approach that has been fruitfully utilised by scholars uncovering the ideological representations created by providers who market UK higher education. The intervention into the marketplace of the selective fee-paying English education of Independent Grammar School: Durham (IGSD) through such a penumbra of symbolic meaning forms part of its pursuit of a competitive edge. International studies of schools chasing prestige and consumer desire confirm that the policies and practices described have become widespread, as shown in the oeuvre of Stephen Ball, whose writings inform the approach of this article. The marketing of the 'brand' identified through our theoretically driven analysis may encourage consumers to opt out of the state sector. Neoliberal-class markers of prestige contribute to the erosion of welfare-oriented school ideals in England, and in other nations.